2006
DOI: 10.1080/03009480500359178
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of high-level glaciofluvial terraces and re-evaluation of the established soil stratigraphy for Early and Middle Pleistocene surfaces, central Yukon, Canada

Abstract: February): Investigation of high-level glaciofluvial terraces and re-evaluation of the established soil stratigraphy for Early and Middle Pleistocene surfaces, central Yukon, Canada. Boreas, Vol. 35, pp. 96 Á/105. Oslo. ISSN 0300-9483.Palaeosols developed on the highest Yukon River glaciofluvial terraces were investigated in order to reconstruct the Plio-Pleistocene evolution of the river valley beyond Late Pleistocene glacial limits. A record of at least two pre-Reid (/311 kyr) glaciations is chronicled by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The lower concentration of smectite in the B horizon compared with the C horizon of McConnell soils suggests that smectite may be unstable in the modern weathering environment. Smectite had been considered diagnostic of older pre-Reid soils by previous researchers (Foscolos et al 1977;Huscroft et al 2006); its formation has been attributed to temperate interglacial climates during the Late Tertiary or Early Pleistocene. Recent research has shown, however, that smectite can form in cool environments and relatively rapidly (Egli et al 2001).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 2 more Smart Citations
“…The lower concentration of smectite in the B horizon compared with the C horizon of McConnell soils suggests that smectite may be unstable in the modern weathering environment. Smectite had been considered diagnostic of older pre-Reid soils by previous researchers (Foscolos et al 1977;Huscroft et al 2006); its formation has been attributed to temperate interglacial climates during the Late Tertiary or Early Pleistocene. Recent research has shown, however, that smectite can form in cool environments and relatively rapidly (Egli et al 2001).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Smectite, characteristic of Wounded Moose soils, was found only in soils on the higher terraces. Huscroft et al (2006) inferred that the two groups of soils record two pre-Reid interglaciations and suggested that the established soil-age relationships and, in turn, their relations to interglacial climates are more complex than previously thought.…”
mentioning
confidence: 98%
See 1 more Smart Citation